INDONESIA - CHINA BILATERAL COOPERATION TO IMPROVE THE QUALITY OF HUMAN RESOURCES IN THE MARITIME SECTOR AS AN EFFORT TO ACHIEVE THE WORLD MARITIME AXIS VISION - Loisa Eunike Lude; Megahnanda Alidyan Kresnawati (Journal Publicuho, 2024)
This study aims to determine the bilateral cooperation efforts that the Indonesian government has carried out to improve the quality of human resources in the country to realize the vision of becoming the world's maritime axis. The Indonesian government recognizes that the country's waters have diverse maritime potential and are essential for world trade routes. If appropriately utilized, Indonesia's territorial waters can become a strategic point for many countries. President Joko Widodo's desire to make Indonesia the world's maritime axis is driven by the realization that Indonesia needs help to achieve this vision because it still has limitations in managing and developing its maritime sector. Therefore, the Indonesian government needs support from other countries, including China, to establish bilateral cooperation. This research is descriptive and uses a qualitative approach. The techniques used in data collection are interviews and data collection from various written sources, such as documents, journals, scientific articles, books, newspapers, reports, and others. The results of this study show that bilateral cooperation carried out by the Indonesian government is bearing fruit because China is also willing to support Indonesia to achieve this vision of the world's maritime axis.